Analisis hubungan antara kualitas layanan jaringan dan pengalaman pengguna pada layanan video streaming youtube - Auliya, Kharisma Xena; Dian W. Chandra (IT Explore: Jurnal Penerapan Teknologi Informasi dan Komunikasi, 2025)
The quality of user experience (Quality of Experience/QoE) in YouTube video streaming services is highly influenced by the quality of network service (Quality of Service/QoS). QoS measurement is conducted using Wireshark software with parameters such as throughput, packet loss, delay, and jitter, and assessed based on the TIPHON standard. Meanwhile, QoE is evaluated through a survey of 30 respondents and measured using the Likert scale.The analysis results indicate that QoS falls into the "Good" category, with a throughput of 1,545.45 kbps at 51.5%, 0% packet loss, 5.69 ms delay, and 0.0015 ms jitter. Additionally, the average QoE score of 4.55 suggests that the user experience is also considered good. Further analysis reveals a correlation between QoS and QoE, where a more optimal network quality positively impacts user experience. These findings provide insights for service providers to optimize streaming quality to meet user expectations.